Performance of Cockerel Fed Hog Plum and Aflatoxin Contaminated Feed - Okusanya, P.O.; Akinlade, O.O. (Nigerian Journal of Animal Science, 2025)
A feeding trial of 42 days was carried out on cockerels to evaluate the curative and ameliorative effect of hog plum when they are fed aflatoxin B1 contaminated feed. One hundred and twenty day old chicks were purchased and randomly allotted into four treatments. At the first three weeks, each treatment received the extract of hog plum (EHP) and Aflatoxin (AF) as follows: Treatment (T) 1: 0 ml of EHP + 0 μi of AF, T2: 1ml EHP, T3: 35 μi of AF + 1ml of EHP, T4: 35 μi AF. At the last three weeks of chick phase, each treatment received: T1: 0 ml of EHP + 0 μi of AF, T2: 35 μi AF+: 0 ml of EHP, T3: 0 ml of EHP + 0 μi of AF, T4: 1ml EHP+ 0 μi of AF. EHP and AF were added per liter of water and kilogram of feed respectively. Data on feed intake, water intake, weight gained, feed conversion ratio and carcass yield were collected and analyzed using One Way Analysis of Variance (ANOVA). There was a significant difference (P<0.05) in parameters measured. T3 had the highest final weight values of 504.50g and the best FCR value of 2.87 at the first three weeks while T4 had the highest final weight during the last three weeks. It was concluded that extract of hog plum enhances growth of cockerel fed aflatoxin contaminated feed and it was recommended to be used a preventive and curative agent of aflatoxicosis in poultry.